Pewadahan Etika Keilmuan di dalam UU Hak Cipta - Moh. Mahfud MD (Fakultas Hukum Universitas Islam Indonesia, 1999)
Some crucial problems related to scientific or academic ethics have been accomodated in Copy Rights Law which provides criminals anactions against the breaker. However, the law could not reach oranticipate all kinds of academic ethicviolations, because some of which had been very difficult to prove juridically